Intraosseous Catheter Flow Rates and Ease of Placement at Various Sites in Canine Cadavers - Lange, James; Boysen, Søren R.; Bentley, Adam; Atilla, Aylin (Frontiers in Veterinary Science, 2019)
Objective: To compare intraosseous catheter placement difficulty, success rates, and flow rates at four different locations in canine cadavers. Design: Prospective study. Setting: Private referral center. Animals: Eleven fresh canine cadavers. Interventions: With owner consent, animals presenting for euthanasia were recruited. Animals received heparin (1,000 IU/kg IV) at least 5 min prior to euthanasia. After euthanasia, EZIO intraosseous catheters were placed into the ilial wing, proximal medial tibia, proximal lateral humerus, and distal lateral femur on one side of the animal. Time to catheter placement and catheter difficulty were scored for each placement site. Sterile saline was infused into each location simultaneously over 5 min, first via gravity then using 300 mmHg pressure. Animals were repositioned onto the contra-lateral side and the experiment repeated. Measurements and Main Results: Placement was successful in 16/22 ilial, 18/22 tibial, and 22/22 femoral and humoral attempts. A post-hoc analysis revealed the ileum had a significantly greater difficulty score when compared to the femur and humerus (p ≤ 0.0001). The femur had a statistically significant faster placement time when compared to the ileum (p ≤ 0.05). Gravity infusion rates were statistically lower in the tibia when compared to humerus (p ≤ 0.01) and between the tibia when compared to the femur (p ≤0.001). Additionally, pressurized infusion rates were statistically lower in the tibia compared to the humerus (p ≤ 0.0001), the femur (p ≤ 0.0001), and the ileum (p ≤ 0.01). Conclusions: The femur and humerus had high success rate for IO catheter placement and low placement time and difficulty scores. Pressurized intraosseous flow rates were highest in the humerus and femur. Contrary to human literature, success rates for catheter placement in the humerus and femur were higher than at other sites, suggesting the humerus and femur may be preferred sites for intraosseous catheter placement in the dog. Further investigation through a larger sample size is required to confirm these findings.